2022
DOI: 10.3389/fpsyg.2022.869646
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Relationship Between Internet Banking and Investment Decision Through Sustainability and Competitive Advantage: Evidence From Congolese Banks

Abstract: Competitive advantage and sustainability emerge as important factors for the success of an organization’s overall differentiation. This research aims to identify the relationship between internet banking and bank investment decision, as well as gaging the mediating effects of sustainability and competitive advantage as attributes of investment decisions. To achieve that, a questionnaire was administrated to banks’ employees and customers. To carry out the hypothesis testing, we have employed structural equatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 94 publications
1
7
0
Order By: Relevance
“…That is, this analysis considers current market attitudes, allowing us to assess how the banking industry responds to innovation for investment decisions. Our findings are further partially consistent with Wu & Pea-Assounga [ 16 ], who showed that fintech is related positively and significantly to sustainability and competitive advantage, which in turn straightened the firms' rational investment choices.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…That is, this analysis considers current market attitudes, allowing us to assess how the banking industry responds to innovation for investment decisions. Our findings are further partially consistent with Wu & Pea-Assounga [ 16 ], who showed that fintech is related positively and significantly to sustainability and competitive advantage, which in turn straightened the firms' rational investment choices.…”
Section: Discussionsupporting
confidence: 91%
“…Yet, not all investments are profitable as the investments’ decision makers do not behave or act sensibly all the time. Many factors, including technological advances, expertise, stakeholder satisfaction, competitive advantage, and sustainability, influence bank investment choices [ 16 , 17 ]. Fundamentally, everyone undertakes investment decisions in life at certain points, whether depositing or saving money, purchasing equipment, insurance, stocks, or constructing infrastructure, and every capital invested implicates risks taken [ 33 ].…”
Section: Review Of Literature and Hypothesis Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, although the studies have addressed crucial aspects of the transition to industry 4.0 in the banking sector, to date, none of them have delved into the relationship between this technological transformation and sustainability from the perspective of banking customers. The intersection between industry 4.0 and sustainable practices represents a relevant field, and understanding how customers perceive and value these aspects can offer valuable insights into the future evolution of the sector [12].…”
Section: Introductionmentioning
confidence: 99%